PHYSICIAN’S ATTITUDE TOWARDS TREATMENT OF OLDER PATIENTS AND THE CHOICE OF THERAPY - Felicetto Ferrara (Mediterranean Journal of Hematology and Infectious Diseases)
The treatment of acute myeloid leukemia in older patients is still object of controversies, because of considerable heterogeneity of patients and disease. Reluctance in administering conventional intensive chemotherapy relies on life-threatening complications induced by treatment in an often frail patient population.  Nonetheless, while there is general consensus on the management of frail patients with supportive care only, a wide area of uncertainty remains for a considerable proportion of patients in whom treatment beyond support is feasible, with the aim of altering the natural history of the disease. Several predictive score have been proposed in order to prevent toxicity in absence of survival advantage, however in the daily practice patients’ and physician attitude do still have a major role in the final therapeutic decision.